Freshwater and its role in the Arctic Marine System: Sources, disposition, storage, export, and physical and biogeochemical consequences in the Arctic and global oceans. Issue 3 (30th March 2016) - Carmack, E. C.; Yamamoto‐Kawai, M.; Haine, T. W. N.; Bacon, S.; Bluhm, B. A.; Lique, C.; Melling, H.; Polyakov, I. V.; Straneo, F.; Timmermans, M.‐L.; Williams, W. J.
Abstract: The Arctic Ocean is a fundamental node in the global hydrological cycle and the ocean's thermohaline circulation. We here assess the system's key functions and processes: (1) the delivery of fresh and low‐salinity waters to the Arctic Ocean by river inflow, net precipitation, distillation during the freeze/thaw cycle, and Pacific Ocean inflows; (2) the disposition (e.g., sources, pathways, and storage) of freshwater components within the Arctic Ocean; and (3) the release and export of freshwater components into the bordering convective domains of the North Atlantic. We then examine physical, chemical, or biological processes which are influenced or constrained by the local quantities and geochemical qualities of freshwater; these include stratification and vertical mixing, ocean heat flux, nutrient supply, primary production, ocean acidification, and biogeochemical cycling. Internal to the Arctic the joint effects of sea ice decline and hydrological cycle intensification have strengthened coupling between the ocean and the atmosphere (e.g., wind and ice drift stresses, solar radiation, and heat and moisture exchange), the bordering drainage basins (e.g., river discharge, sediment transport, and erosion), and terrestrial ecosystems (e.g., Arctic greening, dissolved and particulate carbon loading, and altered phenology of biotic components). External to the Arctic freshwater export acts as both a constraint to and a necessary ingredient for deep convection in the bordering subarctic gyres and thus affects the global thermohaline circulation. Geochemical fingerprints attained within the Arctic Ocean are likewise exported into the neighboring subarctic systems and beyond. Finally, we discuss observed and modeled functions and changes in this system on seasonal, annual, and decadal time scales and discuss mechanisms that link the marine system to atmospheric, terrestrial, and cryospheric systems. Key Points: The Arctic Ocean Freshwater System has major intra‐Arctic and extra‐Arctic effects The Arctic Ocean Freshwater System regulates and constrains physical and biogeochemical processes Changes in the Arctic Ocean Freshwater System are expected in the future with substantial impacts